2017
DOI: 10.1188/17.onf.127-136
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Self-Efficacy, Anxiety, and Health-Related Quality of Life During Chemotherapy: Results From a Longitudinal Study

Abstract: The current study suggests self-efficacy enhancement should be a key component of psycho-behavioral programs designed to support patients with cancer throughout chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 51 publications
4
27
0
2
Order By: Relevance
“…There is an array of evidence to suggest that online interventions can have a positive impact on self-efficacy and patient activation levels [30,32,33,107]. Growing evidence suggests that self-efficacy and patient activation play a significant role in symptom management and quality of life throughout cancer treatment [108,109] and are associated with an array of improved health behaviors and health outcomes [110-112] and lower use of hospital resources [113]. The reviewed systems generally demonstrate positive outcomes for patients as has been found in other reviews [31].…”
Section: Discussionmentioning
confidence: 99%
“…There is an array of evidence to suggest that online interventions can have a positive impact on self-efficacy and patient activation levels [30,32,33,107]. Growing evidence suggests that self-efficacy and patient activation play a significant role in symptom management and quality of life throughout cancer treatment [108,109] and are associated with an array of improved health behaviors and health outcomes [110-112] and lower use of hospital resources [113]. The reviewed systems generally demonstrate positive outcomes for patients as has been found in other reviews [31].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from western societies have identified several factors affecting HRQoL in women with BC. Those factors include socio-demographic characteristics, such as age [9], marital status, economic problems [10], and the experience of daily difficulties in work [11], as well as clinical and psychological characteristics of BC survivors, such as stage of disease [12], pain, stress [13], depression and anxiety [14], social relationships [15], variations in self-confidence, self-efficacy [16], and the development of harmful sentiments. In addition, HRQoL was found to be affected by the therapeutic procedures used [17].A recent review and meta-analysis evaluating the QoL of patients with BC in the Middle East revealed that fewer than one-third of patients (21%) had good QoL [18].…”
mentioning
confidence: 99%
“…We therefore chose a period of 16 weeks assuming that most patients are still under treatment. We also assume that the SN©P might affect patient’s estimation on symptom interference over this period, because patient’s positive attitude for self-management has been shown to be associated with increased physical, emotional and functional well-being over 6 months 53. Other outcomes will include mean changes in symptom intensity, perceived self-efficacy and quality of nursing care assessed four times over a period of 16 weeks.…”
Section: Methods and Analysismentioning
confidence: 99%